Doença Pulmonar Obstrutiva Crônica (DPOC) avaliada em um centro de referência secundário: análise de curso de vida - Verrone, Kelly Cristina Stachewski (2020)
Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death among chronic diseases in Brazil and its development is multifactorial. Comprehensive care for these individuals prevents severe future pulmonary obstruction. The objectives of the present study are to describe the epidemiological characteristics and factors associated with COPD in patients attended by the public health system in Sorocaba (SP) and to propose a matrix flowchart for systematization and qualification of referrals for specialized consultations. Method: A cross-sectional and analytical study, with a quantitative approach, which evaluated participants with COPD (≥ 18 years old); classified by the degree of obstruction to spirometry, according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD); and by the severity of dyspnea on the modified British Medical Research Council (mMRC) scale; from March 22nd to September 4th, 2019. The research was approved by the Ethics Committee of PUC-SP under CAAE: 07819219.7.0000.5373. To check the relationship between degree of obstruction and GOLD classification, a Chi-square test was used. Epidemiological characteristics and factors associated with COPD were collected and are presented within a participant's life course model. Hierarchical logistic regression models were applied to assess factors associated with severe obstruction. The software used for data analysis was Stata®, version 15.1. The study included 140 patients with an average age of 62 years, 78 of whom were female. Of the total number of COPD patients, 43 (30.7%) reported childhood asthma and, currently, 126 (90%) had dyspnea; 96 (68.6%) asthma and 48 (34.3%) another lung disease, with the presence of asthma in some cases. In addition, 40 (28.6%) of the patients smoked and 54 (38.6%) were former smokers. Patients with diabetes (OR 2.87; CI 1.16-7.06) who reported to be currently smokers (3.33; CI 1.19-9.26) or had smoked in the past (OR 2.95; CI 1.13 -7.71) were more likely to have severe obstruction. Childhood asthma was shown to be a protective factor (OR 0.39; 0.15-0.99). The smoking habit stood out, among the others, as an important associated factor for the development of COPD. People with COPD who never smoked, childhood asthma was a protective factor against the severity of the disease, possibly because childhood asthmatics opted for habits and / or workplaces that would not worsen the natural history of the disease during their existence. The lifeline composition to understand the life course of the individual with COPD provided a broad and comprehensive understanding of the disease. In turn, understanding the natural history of COPD, its epidemiological characteristics and its triggering factors, allowed us to build a flowchart aiming to educationally forward the referrals to the specialist and, thus, prevent its most serious outcomes